2020
DOI: 10.1002/der2.32
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective chart review of subdermal neck coagulation using helium plasma technology

Abstract: Background A helium‐based plasma technology has recently been cleared by the Food and Drug Administration for cutting, coagulation, and ablation of soft tissue (Renuvion® System; Apyx™ Medical Corporation). As the safety of helium plasma for treating lax and sagging skin in the neck area has not been previously reported, the objectives of this study were to obtain safety results from helium plasma used for neck rejuvenation, to summarize subject and procedure variables, and to assess treatment outcomes for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Given interpatient variability in available FSN substrate, establishing clinical guidelines for consistent and predictable results is proving challenging. Recent single and multi-center chart reviews have demonstrated high patient satisfaction along with the safe and effective use of Renuvion® as an adjunct to enhance liposuction outcomes [21,29,30]. Consistent and reproductible soft tissue contraction was demonstrated even in the clinically challenging area of the neck area by subjective and quantitative analyses of before and after photographs [21].…”
Section: Physics and Mechanics Of Renuvion®mentioning
confidence: 99%
See 2 more Smart Citations
“…Given interpatient variability in available FSN substrate, establishing clinical guidelines for consistent and predictable results is proving challenging. Recent single and multi-center chart reviews have demonstrated high patient satisfaction along with the safe and effective use of Renuvion® as an adjunct to enhance liposuction outcomes [21,29,30]. Consistent and reproductible soft tissue contraction was demonstrated even in the clinically challenging area of the neck area by subjective and quantitative analyses of before and after photographs [21].…”
Section: Physics and Mechanics Of Renuvion®mentioning
confidence: 99%
“…It creates a direct discharge, non-equilibrium, low temperature plasma beam at atmospheric pressure as helium gas is passed over a sharp, conductive point held at high voltage and high frequency. The system consists of a RF generator, supply of helium gas and an electrode within the tip of a handpiece [21]. The generator operates at a maximum of 4.0 kV, 40 Watts and 490 kHz frequency [22].…”
Section: Physics and Mechanics Of Renuvion®mentioning
confidence: 99%
See 1 more Smart Citation
“…Renuvion (Apyx Medical, Clearwater, FL, USA) combines radiofrequency energy and helium plasma to create subdermal tissue contraction. The device reaches the optimal temperature for subdermal tissue contraction (85°C) quickly with minimal thermal spread and cools to baseline temperatures in less than a second [40][41][42][43][44][45].…”
Section: Renuvion Helium Plasma-driven Radiofrequency (Apyx)mentioning
confidence: 99%
“…The advantages of the Renuvion system are decreased procedure times, decreased pain, and decreased risk of complications [39,[45][46][47][48][49]. The measured skin temperature rarely exceeds 38°C, leading to its increased safety profile.…”
Section: Renuvion Helium Plasma-driven Radiofrequency (Apyx)mentioning
confidence: 99%